Implementing Lean Management in catering operations: limits and perspectives - Walentynowicz, Piotr; Ostrowska, Paula (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The article presents considerations on the benefits of using Lean Management in the catering industry, especially in the conditions of the current economic downturn. The main purpose of the article is to present the idea of Lean Management in the catering business, the main types of waste that can occur in this activity and the basic Lean solutions that can help eliminate these inefficiencies. The article also indicates three basic models of Lean in restaurant operations developed in an original way based on empirical research carried out using the case studies method. An additional research method was the method of analysis and synthesis of literature sources. The benefits that the use of Lean Management at a high level of professionalism can bring to this type of activity have been identified. The main limitation of the study is that it is conducted on a limited number of entities. However, based on the results of the study, the authors sincerely recommend that executives and restaurant owners take an interest in this management concept.